2003
DOI: 10.1017/s027226310300024x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relative Effectiveness of Structured-Input and Output-Based Instruction in Foreign Language Learning

Abstract: This paper reviews studies that have contrasted the effectiveness of structured-input instruction with output-based instruction. It then presents results from a study comparing the relative effects of structured-input and output-based instruction on students' ability to comprehend and produce direct object pronouns in second language French. Three classes of students (N = 70) were assigned to three groups: structured-input instruction, output-based instruction, and control. Students were assessed on listening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 24 publications
2
45
0
1
Order By: Relevance
“…Not all studies in the literature, however, have found advantages of PI compared to other instructional types; this is the case for Spanish direct object pronouns and the conditional (DeKeyser & Sokalski, 1996), Spanish direct object pronouns (Keating & Farley, 2008;Morgan-Short & Bowden, 2006;Salaberry, 1997), Japanese honorifics (Nagata, 1998), French causative instruction (Allen, 2000), French direct object pronouns (Erlam, 2003), Spanish anticausative clitic se (Toth, 2006), and English present subjunctive (Farley & Aslan, 2012). All these studies, contrary to earlier PI studies, found that on the interpretation task, either the PBI and PI groups scored equally, or PBI performed better than PI; additionally, on the production task, the PBI group performed much better than PI.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
“…Not all studies in the literature, however, have found advantages of PI compared to other instructional types; this is the case for Spanish direct object pronouns and the conditional (DeKeyser & Sokalski, 1996), Spanish direct object pronouns (Keating & Farley, 2008;Morgan-Short & Bowden, 2006;Salaberry, 1997), Japanese honorifics (Nagata, 1998), French causative instruction (Allen, 2000), French direct object pronouns (Erlam, 2003), Spanish anticausative clitic se (Toth, 2006), and English present subjunctive (Farley & Aslan, 2012). All these studies, contrary to earlier PI studies, found that on the interpretation task, either the PBI and PI groups scored equally, or PBI performed better than PI; additionally, on the production task, the PBI group performed much better than PI.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
“…Another strand of research~Allen, 2000; Collentine, 1998;DeKeyser & Sokalski, 1996;Erlam, 2003;Nagata, 1998;Salaberry, 1997! focused on the exploration of any differential effects of input-based as compared to output-based instructional conditions+ Accordingly, much of this research has made attempts to methodologically isolate the variable of output+ Specifically, these studies have compared the effects of some type of input practice~often labeled PI!…”
Section: Studies Examining Relative Effects Of Input and Outputmentioning
confidence: 99%
“…they did not provide explicit information designed to alter any learner processing strategy~DeKeyser & Sokalski, 1996;Erlam, 2003;Nagata 1998!,~b! they~either intentionally or unintentionally!…”
Section: Studies Examining Relative Effects Of Input and Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…La ricerca sembra indicare che gli effetti delle structured input activities non riguardano solo la comprensione delle LE, 6, 3, 2017, 363-384 e-ISSN 2280-6792 costruzioni linguistiche target, ma hanno anche un riflesso nella produzione linguistica degli apprendenti a cui vengono somministrate (Cadierno 2010). Inoltre, sembra accertato che le cosiddette structured output activities (Lee, VanPatten 1995;VanPatten 1996), cioè le attività mirate alla produzione controllata dell'output degli studenti e complementari a quelle centrate nel passaggio dell'input all'intake, abbiano una ricaduta positiva nella capacità degli studenti di produrre le costruzioni linguistiche (Erlam 2003;Morgan-Short, Wood-Bowden 2006). Bisogna tener presente che l'uso autonomo delle costruzioni linguistiche diventa particolarmente difficile nel caso di chi presenta limitazioni nell'elaborazione rapida ed efficiente delle informazioni.…”
Section: Il Potenziale Glottodidattico Della Linguistica Cognitivaunclassified